Increasing Students’ Interest in Learning Throught Online Learning - Sofwan Manaf; Samiyono; Mastur, Mastur; Intan Rahana; Apriani Putri; Ainur Rohimah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Online learning is one of the learning alternatives that can reach many students. However, whether online learning can increase students’ interest in learning, this is the focus of this research, how much influance online learning has on students’ interenst in learning. Using descriptive quantitative approach involving 68 student of Darunnajah University. The survey collection technique uses goole form with analysis of survey result using smartPLS. The results showed that online learning has a significant positive effect on student interest in learning, seen from the t-statistic value of 14,006 greater than the t-tabel of 1,967 and the p value of 0,000 smaller than 0,05. Meanwhile, the effect of online learning on student interest in learning is 57,8%, while the rest is influanced by variables not examined.